STRATEGIES FOR IMPLEMENTING E-RECRUITMENT IN START-UP COMPANY - Abin Devandra; Devia Pratiwi; Dea Ananda; Muthia Naila Nasution; Novi Aulia Safina (International Conference on Health Science, Green Economics, Educational Review and Technology, 2024)
This research is important to help start-up companies optimize the recruitment process through e-recruitment, which can increase efficiency, save costs, and accelerate candidate selection. By leveraging digital technology, companies can face the challenges of limited resources and still attract the best talent. which can increase the competitiveness of the company in a competitive market.The purpose of this study is to analyze the strategy of implementing e-recruitment in startups that are currently the most successful in the business world. Along with the development of information technology, many startups that deviate from traditional recruitment methods use digital platforms to recruit and evaluate candidates efficiently. This study examines various strategies that can be applied by startups to optimize the e-recruitment process, in addition, this research highlights the challenges and obstacles faced by startups when implementing e-recruitment. The use of the method in this study is a qualitative method explained through approaches such as in-depth interviews, participatory observations, thematic analysis, and case studies to analyze the implementation strategy of e-recruitment in start-up companies. The results of this study identify various factors that affect the implementation of e-recruitment in start-up companies, including technology infrastructure, organizational culture, digital skills, challenges faced, and flexible strategies implemented in the recruitment process.